Struktur Komunitas Makroalga di Pantai Pandawa, Bali - Putri, Anak Agung Raka Triyana; Pebriani, Dewa Ayu Angga; Watiniasih, Ni Luh (Journal of Marine and Aquatic Sciences; Vol 9 No 1 (2023), 2023)
Macroalgae are classified as low-level plants ( thallophyta ), no have vascular and have a vegetative body that has not recognized the differentiation of the roots, stems and leaves, so it is called a thallus . This aims to determine the diversity of macroalgae species and the percentage of maroalgae cover in the waters of Pandawa Beach. The research was conducted for 2 months from January-February 2021. This study used a descriptive method with a quantitative approach. The data were collected at 3 stations using the 1x1 m 2 quadrant transect of method. The results of the study found 17 types of macroalgae on Pandawa Beach including Halimeda macroloba , Padina australis , Ulva lactuca , Palmaria palmata , Galaxaura rugosa , Laurencia papillosa , Gracilaria textorii , Turbinaria deccurrens , Halimeda opuntia , Kappaphycus alvarezii, Gracilariopsis longissimi , Chondrococcus hornemannii , Amphiroa fragilissima , Chondrus crispus , Halymenia floresii , Amphiroa rigida , and Phyllophora crispa . The highest abundance value of macroalgae species was Laurencia papillosa species with a total of 2,87 individuals/m 2 . Based on the results of the calculation of the diversity index value on Pandawa Beach is 1,44-2,02 so it is included in the medium category. The uniformity index value on Pandawa Beach is 0,69-0,87 so it is included in the medium category. The dominance index value on Pandawa Beach is classified as a low category with a value of 0,17-0,28. The highest percentage value of macroalgae cover on Pandawa Beach was Laurencia papillosa with 0,53-2,87%.